Determination of 1-chloro-2,3-epoxypropane in order to assess the working environment - Anna Jeżewska; Dorota Kondej; Agnieszka Woźnica (Nofer Institute of Occupational Medicine, 2020)
Background 1-Chloro-2,3-epoxypropane, known as epichlorohydrin (ECH), is a colorless liquid used in the production of epoxy resins, synthetic glycerine, elastomers, glycidyl ethers, surfactants, polyamide-epichlorohydrin resins and others. Epichlorohydrin may cause cancer. The aim of this study was to develop a new method for determining concentrations of ECH in workplace air in the range of 1/10-2 values of the maximum admissible concentration (MAC). Material and Methods The paper presents a method for the determination of ECH in workplace air using a gas chromatograph coupled with a mass spectrometer (GC-MS). The developed method is based on the adsorption of ECH on an activated charcoal, extraction with acetone, and a chromatographic analysis of the resulting solution. Results The method developed makes it possible to determine ECH in the concentration range of 0.1-2 mg/m 3 , i.e., 1/10-2 values of MAC established in Poland. The limit of detection (LOD) is 0.24 μg/m 3 and the limit of quantification (LOQ) is 0.71 μg/m 3 . Conclusions The method is characterized by good precision and accuracy; it meets the requirements of the European standard PN-EN 482, and can be used by occupational hygiene laboratories to measure concentrations of ECH in workplace air, with a view to assessing workers' exposure to this substance. Med Pr. 2020;71(6):715-23